2021
DOI: 10.1097/htr.0000000000000733
|View full text |Cite
|
Sign up to set email alerts
|

Postconcussion Symptoms After an Uncomplicated Mild Traumatic Brain Injury in Older Adults: Frequency, Risk Factors, and Impact on Quality of Life

Abstract: Background: Postconcussion symptoms (PCSs) are common complaints reported by patients after a mild traumatic brain injury (TBI), and these symptoms may lower quality of life. Previous investigations have primarily focused on PCSs in children, adults, and athletes. The frequency, and risk factors, and effects of PCSs for older adults with mild TBIs are unclear. Purpose: To investigate the frequency and risk factors of PCSs, and investigate their effects on quality of life over time after mild TBI in older adult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…Fourth, since this study was part of the UPFRONT study, a separate sample size calculation was not conducted for the HRQoL questionnaire and its subdomains. However, when considering other studies examining older adults and HRQoL, our group is comparable or even larger [38,54,55]. Therefore, we believe that our sample size was sufficient to provide a reliable assessment of HRQoL, although we might have lacked power for detecting differences at the subdomain level.…”
Section: Discussionmentioning
confidence: 93%
“…Fourth, since this study was part of the UPFRONT study, a separate sample size calculation was not conducted for the HRQoL questionnaire and its subdomains. However, when considering other studies examining older adults and HRQoL, our group is comparable or even larger [38,54,55]. Therefore, we believe that our sample size was sufficient to provide a reliable assessment of HRQoL, although we might have lacked power for detecting differences at the subdomain level.…”
Section: Discussionmentioning
confidence: 93%
“…29,30 One study indicated that PCS may decrease quality of life, especially in the elderly; frequently reported symptoms over time were dizziness, sleep disturbances, fatigue, and forgetfulness. 31 The strengths of the study include the high response rate and overall completeness of data. A potential weakness may be that many of the respondents are ED doctors and may lack complete knowledge regarding observation routines and follow-up.…”
Section: Discussionmentioning
confidence: 99%
“…As only a subset of patients have issues with postconcussion syndrome (PCS), predictive scores may be useful to identify which patients may benefit from a structured follow‐up 29,30 . One study indicated that PCS may decrease quality of life, especially in the elderly; frequently reported symptoms over time were dizziness, sleep disturbances, fatigue, and forgetfulness 31 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Emotional symptoms can include depression, frustration, or restlessness. 4 A study investigating 2-week and 6-month recovery outcomes based on the Glasgow Outcome Scale-Extended Score showed that 73% of respondents demonstrated incomplete recovery at 2 weeks and 56% of respondents demonstrated incomplete recovery at 6 months.…”
Section: Introductionmentioning
confidence: 99%